2017
DOI: 10.1093/nar/gkx639
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy between nucleases required for homologous recombination promotes PARP inhibitor resistance in the eukaryotic model organism Dictyostelium

Abstract: ADP-ribosyltransferases promote repair of DNA single strand breaks and disruption of this pathway by Poly(ADP-ribose) polymerase (PARP) inhibitors (PARPi) is toxic to cells with defects in homologous recombination (HR). Here, we show that this relationship is conserved in the simple eukaryote Dictyostelium and exploit this organism to define mechanisms that drive resistance of the HR-deficient cells to PARPi. Dictyostelium cells disrupted in exonuclease I, a critical factor for HR, are sensitive to PARPi. Dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Treatment of D. discoideum with the PARP inhibitor NU1025 leads to chromatin recruitment of the HR protein Rad51, indicating that, similar to humans, DNA damage induced by PARP inhibitors is repaired by HR. Consistent with this model, strains lacking the nuclease Exo1 that are defective in HR, show synthetic lethality with PARP inhibitors (Kolb et al, 2017). The conservation of this phenomenon with humans makes D. discoideum an attractive system to identify mutations which lead to resistance of HR-deficient strains to PARP inhibitors and therefore potentially cause resistance of tumors to PARP inhibitor treatment.…”
Section: Targeting Of Adp-ribosyl Transferases In Cancermentioning
confidence: 72%
See 1 more Smart Citation
“…Treatment of D. discoideum with the PARP inhibitor NU1025 leads to chromatin recruitment of the HR protein Rad51, indicating that, similar to humans, DNA damage induced by PARP inhibitors is repaired by HR. Consistent with this model, strains lacking the nuclease Exo1 that are defective in HR, show synthetic lethality with PARP inhibitors (Kolb et al, 2017). The conservation of this phenomenon with humans makes D. discoideum an attractive system to identify mutations which lead to resistance of HR-deficient strains to PARP inhibitors and therefore potentially cause resistance of tumors to PARP inhibitor treatment.…”
Section: Targeting Of Adp-ribosyl Transferases In Cancermentioning
confidence: 72%
“…For example, this approach demonstrated that resistance to PARP inhibitors observed by disrupting NHEJ in an exo1 − background (dnapkcs − exo1 − cells) is mediated by promoting end-resection to reactivate HR. Small molecule inhibitors of Mre11, a second nuclease involved in strand resection during HR, restores sensitivity of dnapkcs − exo1 − cells to PARP inhibitors (Kolb et al, 2017). This highlights redundancy between the nucleases Exo1 and Mre11 in HR and suggests combination approaches to avoid resistance in cells deficient in one nuclease.…”
Section: Targeting Of Adp-ribosyl Transferases In Cancermentioning
confidence: 87%
“…The h3b − , adprt1a − adprt2 − , ku80 − and e xo1 − strains have been previously described 35 , 37 , 38 , 42 , 45 . The Flag-Rad51 expression plasmid has been previously described 42 .…”
Section: Methodsmentioning
confidence: 99%
“…The role of cisplatin on gene expression in the model has been analysed (Van Driessche et al, 2007), in addition to its regulation of mitogen activated protein kinase phosphatases (Moncho-Amor et al, 2011) and in DNA repair pathways (Gunn et al, 2016). The cellular functions of other anti-cancer treatments, such as bestatin and Poly (ADPribose) polymerase inhibitors have also been analysed in D. discoideum (Kolb et al, 2017, Poloz et al, 2012. Finally, Dictyostelium strains have also been shown to provide a source of novel compounds with anti-proliferative properties that could thus be used as cancer treatments (Honma et al, 2018, Kubohara and.…”
Section: Treating Cancer: Lessons From D Discoideummentioning
confidence: 99%